MHD two‐phase flow of Jeffrey fluid suspended with Hafnium and crystal particles: Analytical treatment - Nazeer, Mubbashar; Hussain, Farooq; Khan, M. Ijaz; Shahzad, Qasiar; Chu, Yu‐Ming; Kadry, Seifedine (Numerical methods for partial differential equations, 2024)
This article offers a comparative investigation for Newtonian and non‐Newtonian multiphase flows drifting through an inclined channel. A non‐Newtonian Jeffrey fluid is used as the base fluid. However, Hafnium particles and crystal particles are considered to form two different kinds of two‐phase suspensions. Each flow comes under the influence of an external and transversely applied magnetic force. The effects of gravitational force have also been taken into account which is the main source of the supercritical flow. Flow dynamics are modeled with the help of Navier–Stokes. A closed‐form solution is achieved by invoking the analytical technique subject to, no‐slip condition at the boundary of the channel. A detailed parametric study, regarding the contribution of pertinent variables, is carried out in the graphical section. Furthermore, the obtained analytical and visual results have been vetted numerically through different tables, as well. The findings reveal that non‐Newtonian biphase flows are more significant than Newtonian biphase flows. Similarly, Jeffrey fluid is much suitable for multiphase flows and Hafnium particle suspension with Jeffrey fluid is much better than the one obtained by the crystal‐Jeffrey suspension. Finally, Hafnium suspends well with non‐Newtonian fluid. Such alloys are more suitable for mechanical purposes, particularly for nuclear reactors as coolants. In addition to this, no comparative analysis between Newtonian and non‐Newtonian multiphase flows has so far been reported in the existing literature.